Multivariant Crystallization of Tetraplatin Precursors from Solutions Containing 1,2-C6H10(NH3)2 2+ and [PtCl6]2– Ions - R. F. Mulagaleev; D. Y. Leshok; A. K. Starkov; A. N. Matsulev; S. D. Kirik (Journal of Chemistry)
Seven new phases containing hexachloroplatinate [PtCl6]2− and trans-1,2-dl-diammoniumcyclohexane 1,2-C6H10NH322+ ions were obtained by crystallization from solutions with minor variation of synthesis conditions. The compounds can be applied as precursors for the synthesis of effective anticancer drug tetraplatin ([PtC6H10(NH2)2Cl4]). The phase diversity was achieved by alterations including solvent acidity, crystallization rate, temperature, type of solvent, and the reagents ratio. The compounds were characterized by chemical and thermal analysis, IR, and 1H NMR spectroscopy. Crystal structures of the five compounds were determined by X-ray powder diffraction technique. The phases have ionic structures involving H2O, HCl molecules, or Cl− ions as supplementary species in the lattices. It helps to arrange some frames additionally interconnected by hydrogen bonds between ions and solvent molecules. It was suggested that crystal lattices adapted associated particles presented in solutions. It results in observed variety of the crystal structures. Besides the basic interest the obtained results are important for tetraplatin synthesis control.